Desenvolvimento, pobreza e segurança alimentar na América do Sul - Azevedo, Ludmila Luísa Tavares e (2017)
Based on the emergence and importance of the hunger problem in the world, this dissertation sought to understand the concepts and relation of development, poverty and food security in South America one of the regions that presented the best results in the battle against hunger throughout the last decades. From the perspective of human development, we intend to understand if there is a direct and unequivocal relationship between thesethree variables. Therefore, we present these concepts and their particularities, as well as illustrative data of the situation in South America. Moving on to the understanding of food security, our work analyzes not only this concept, but also presents the results of the Millennium Development Goals and some debates on the Human Right to Adequate Food as well as the modus operandi of the agricultural markets two issues in dispute and that are part from the structure of the reproduction of the problem. In addition, the work analyzes the public policies carried out by the countries of the region in order to solve the hunger problem. Likewise, in order to identify the economies where food insecurity is most acute and understand the dimension that most impacts the problem, ourwork used the variables proposed by the FAO for food security, applying a Principal ComponentAnalysis on two of the four dimensions (availability, access), separately, and a descriptive analysis for stability and utilization, dimensions in which the method cannot be applied. Finally, we present comparative rankings between GDP per capita, HDI, and percentage of undernourished people living below the poverty line of the World Bank. It was concluded that, despite the similarity of the rankings, and for all the analyses made during the course of the study, Food Security is a phenomenon with its own complexity, which cannot only be fought by an increase in income or food supply, or with poverty eradication. Understanding its complexity leads us to conclude that it is a concept that must continue to be exhaustively studied so that its combat can occur in a conscious and articulate way.